The Unholy Alliance of Islamic Populism and Political Entrepeneur in Jakarta Election: The Aftermath Implications - Akmaliah, Wahyudi; Nadzir, Ibnu (DINIKA : Academic Journal of Islamic Studies, 2021)
In the early years of Reform Era, Islam in Indonesia was portrayed as the representation of moderate Islam. While some scholars argue that Islam in Indonesia has strong ties with religious commodification, Indonesia also often presented as the best practice where Islam could work with democracy. At that time, even Islamist groups were never really considered as a real threat to Indonesian democracy, mainly because their activities were mostly described as fragmented and sporadic. In that context, the Jakarta election brings new dynamic as part of the discussion on Islamization in Indonesia after the fall of the New Order. The blasphemy case of Ahok has become a trigger for a series of demonstration that illustrates the strength of political Islam ideology in shaping current Indonesian public sphere. To discuss these recent developments the article revisits the discourse of Islamization in Indonesia. We argue that intertwine between commodification of religious symbols, the use of new media, and political interest serves as the background of the unholy alliances between religious elites and political entrepreneurs in Jakarta election. As a consequence, the event of the Jakarta election has become a critical juncture where the emergence of Islamic populism has threatened both the notion of Indonesian democracy and the existence of moderate Moslem as well.Â